The Effect of Genre Approach to Improve University Students’ Critical Thinking Skills - Gunawan Ismail; Helaluddin Helaluddin (STAI Hubbulwathan Duri, 2022)
This study aims to determine the impact of using a genre-based approach on students’ critical thinking skills through learning to write essays. This study uses a quasi-experimental design involving 54 students (experimental and control classes) taking writing course one at the Indonesian Language and Literature Education Study Program, Muhammadiyah University of Palembang, South Sumatra, Indonesia. Data were collected using a written essay test which was then assessed using the critical thinking skills assessment rubric. The collected data were analyzed using SPSS 20.00 by performing paired sample t-test, independent sample t-test, and MANOVA. The group of students who used the genre approach was proven to improve critical thinking skills compared to the group that used the conventional method. Thus, it is hoped that teachers can consider this genre approach as an alternative learning method for improving students’ critical thinking skills.